ANALISIS KESALAHAN PREPOSISI PADA TEKS DESKRIPSI OLEH SISWA MADRASAH ALIYAH NURUL HUDA DOWORA DI TIDORE - MUTMAINNA, WAHYUNI WULANDARI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This research entitled â€œAn Error Analysis of Prepositions in Descriptive Texts Made by Students of Madrasah Aliyah Nurul Huda Dowora in Tidoreâ€ is an attempt to classify, analyze and descripe the errors in the use of prepositions in descriptive texts. It was carried out at Madrasah Aliyah Nurul Huda Dowora in Tidore. The method used in this research is descriptive. Aarts and Aartsâ€™ (1982) concept is used to explain the types of prepositions. To find out the kinds of error in Â prepositions made by the students. Jha (1991) theory is used to explain the types errors in prepositiosn made by the students.. The data of the research were taken from the studentsâ€™ writing assignment.Â Â Â Â Â Â Â Â Â The results of this research show that there are three kinds of preposition errors made by the students. First, the omission of preposition-the students drop a preposition in a sentence where it is obligatory. Second, the insertion of preposition-the students add a preposition in a sentence where it is not necessary. Third, the selection of incorrect preposition ed in a sentence. Â Â Keyword : Error analysis, prepositions, omission, insertion, selection.